A Crux in the Proem of Henry of Avranches’ Bordo-Siler (R 129–144,17–18) - Adkin, Neil (Acta Classica Universitatis Scientiarum Debreceniensis, 2022)
The 13th-century poet Henry of Avranches has given us in the form of his Bordo-Siler what is a chef-d’oeuvre of poetic vituperation. The proem of this important poem is marred by textual corruption in the view of its editor and commentator, A. G. Rigg. The present article endeavours to show that the text is sound. Here we in fact have a reference to the parable of the Prodigal Son. We also have a clever jeu grammatical in the matter of metrical quantity.